Hybrid Cryptography Based on Planets: Phobos & Deimos - Kraicha Ayoub; Touil Hamza; El Akkad Nabil (E3S Web of Conferences)
Data protection is now a top priority for organizations, especially with the evolution of information systems and the challenges posed by modern technology. Remote access has become essential for business continuity but also introduces significant security risks. To address these issues, it is crucial to innovate in cryptography, the backbone of data security. This document presents the Phobos and Deimos encryption method, inspired by Mars’ moons. By using the unique orbital properties of Phobos and Deimos, this method creates a dynamic encryption algorithm. The approach involves dividing the alphabet into groups and applying shifting techniques based on Deimos’ positions, enhancing data security through increased complexity. The Phobos and Deimos encryption method aims to provide a robust solution for safeguarding sensitive information, ensuring confidentiality, integrity, and authenticity in today’s digital landscape.